Cancer mortality among shoe manufacturing workers: an analysis of two cohorts. Issue 6 (June 1996) - Fu, H; Demers, P A; Costantini, A S; Winter, P; Colin, D; Kogevinas, M; Boffetta, P
Abstract : OBJECTIVES: To examine the cancer risk of shoe manufacturing workers and evaluate whether the risk was associated with exposure to leather dust and solvents. METHODS: Data from two historical cohort studies of shoe workers were expanded and analysed in parallel. A total of 4215 shoemakers from England contributing 103 726 person-years at risk and 2008 shoemakers from Florence, Italy, contributing 54, 395 person-years at risk were included in the analysis. Exposure to leather dusts and solvents from glues was evaluated on the basis of job title information. Standardised mortality ratios (SMR) were calculated as ratios of observed deaths (Obs) over expected derived from national mortalities. RESULTS: Overall mortality was lower than expected in both cohorts (English cohort: Obs 3314, SMR 81, 95% confidence interval (95% CI) 78-84; Florence cohort: Obs 333, SMR 87, 95% CI 78-97). An increased risk of nasal cancer was found (English cohort: Obs 12, SMR 741; Florence cohort: Obs 1, SMR 909). 10 of the 13 cases occurred among English workers employed in the manufacture of welted boots (SMR 926, 95% CI 444-1703), a sector of the industry thought to have had the highest exposure to leather dust. Mortality from leukaemia was not increased in the English cohort (Obs 16, SMR 89), but was increased in the Florence cohort (Obs 8, SMR 214, 95% CI 92-421); and the highest risk was found among shoe workers in Florence who were first exposed between 1950 and 1959 when exposure to benzene was substantial (Obs 3, SMR 536, 95% CI 111-1566). Some evidence for an excess risk of stomach, bladder, and kidney cancer, as well as multiple myeloma and non-Hodgkin's lymphoma was also found in the Florence cohort only among workers employed in jobs with the highest exposure to solvents. CONCLUSIONS: These findings confirm the associations between exposure to leather dust and nasal cancer and between exposure to benzene and leukaemia in the shoe manufacturing industry and suggest that the risk of other cancers may be increased among workers exposed to solvents or glues.